Synthesis of heterocycle-substituted bicyclo[3.1.1]heptanes and aza-bicyclo[3.1.1]heptanes via photocatalytic minisci reaction - Revie, RI; Whitaker, BJ; Paul, B; Smith, RC; Anderson, EA (American Chemical Society, 2024)
A route toward heterocycle-functionalized bicyclo[3.1.1]heptanes (BCHeps) and aza-bicyclo[3.1.1]heptanes (aza-BCHeps) has been developed, using mild, photocatalytic Minisci-like conditions to introduce various heterocycles at the bridgehead position from readily available N-hydroxyphthalimide esters of the corresponding carboxylic acids. This chemistry enables access to heterocycle-functionalized BCHep-containing structures that are highly relevant in medicinal chemistry research as potential bioisosteres of meta-substituted arenes and pyridines.